Supply chain optimization of sustainable aviation fuel from carinata in the Southeastern United States. (January 2023) - Masum, Farhad Hossain; Coppola, Ed; Field, John L.; Geller, Daniel; George, Sheeja; Miller, Jonathan L.; Mulvaney, Michael J.; Nana, Sanjay; Seepaul, Ramdeo; Small, Ian M.; Wright, David; Dwivedi, Puneet
Abstract: Carinata is a purpose-grown oilseed feedstock for renewable fuels, including sustainable aviation fuel (SAF) that can replace conventional aviation fuel (CAF). Given carinata is a new crop in the Southeastern United States, it is crucial to analyze its sustainability from a supply chain perspective. This study developed a mixed-integer linear programming (MILP) model and simulated it for 20 years, starting from a farm (county-level data) and ending at the airport. About 2.06 million ha in Alabama, Florida, and Georgia combined were found suitable for carinata production. Given the three-year rotation period, about 0.69 million hectares can be cultivated annually, approximately 65% of which was in Georgia. About 2.4% of the combined SAF annual demand of four major airports (about 210 thousand t) in the study area is satisfied at that level of carinata cultivation. However, all available SAF was supplied to the Atlanta airport as this decision minimizes the supply chain cost. A total of 1343 storage units, one oil extraction mill, and one biorefinery were needed to meet the overall demand. We found that SW Georgia is the top supplier of carinata seeds. The unit cost of production and carbon intensity were estimated to be 0.89 L -1 (or 26.79 GJ −1 ) and 0.91 kg CO2 e L −1 (or 27.28 kg CO2 e GJ −1 ), respectively. This carbon intensity of carinata-based SAF was 67.8% lower than that of CAF. With variations included in SAF demand, yield, and soil carbon sequestration, carbon savings remained between 66.5% and 67.8%. Given the GHG advantage of SAF over CAF, there is justification for subsidies required to make SAF competitive. Graphical abstract: Image 1 Highlights: A supply chain optimization framework for sustainable aviation fuel (SAF) is presented. Potential carinata cultivation area and yield in the Southeastern United States is reported. Optimal material flows of seed, oil, and fuel for SAF production are reported. Cost (0.89 L -1 ) and carbon emissions (0.91 kg CO2 e L −1 ) of SAF are estimated. About 206 per metric ton of CO2 abated would be necessary to make SAF competitive.